Structural Contradictions Between Energy Production and Consumption Along With Economic Development and Environmental Protection in China: Evidence and Policy Implications - Tang, Erzi (Frontiers in Environmental Science, 2022)
This paper empirically describes and analyzes the structural contradictions between energy production and consumption in the Chinese local economy. Alongside rapid economic growth, energy usage in China increased gradually and exceeded energy production for a long time. For some particular energy sources such as petroleum, the gap between supply and demand is relatively larger than that of the whole energy sector in the economy. The process of turning fossil fuels into final energy products for use causes a great deal of pollution, especially emitting industrial waste gases, such as particulate matter emission, into the atmospheric environment. Increasing energy production directly and greatly to solve the gap between energy supply and demand in the economy may impact environmental quality and not meet sustainable development needs. It is difficult to coordinate energy production and consumption when considering economic development and environmental protection in economic operation. Importing energy could meet the excess energy consumption in a short period but often fluctuates from foreign energy market changes and global political events. For policy recommendations, some policies which directly lower energy consumption may impact economic development since industry is the main consumer of energy, and industrial production is an important component of GDP in China. Declining the role of the industry sector in the economy and reducing industrial product exports, including some energy-intensive products, could solve the structural contradictions between energy production and consumption under the condition of maintaining economic development and protecting the environment in China, but this is a long-term adjustment process.